Phytosociological Study of Macrophytes in a Polluted Pond of Shahjahanpur (India)ï€ - Atul Namdeo, Saltanat Ara Malik and (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Abstract A phytosociological Study of Macrophytes was conducted in the present investigation in a Polluted Pond of Shahjahanpur area in India. Please Cite This Article As: Â  Saltanat Ara Malik and Atul Namdeo. 2010. Phytosociological Study of Macrophytes in a Polluted Pond of Shahjahanpur (India). J. Exp. Sci. 1(5):01-03. Â 